2010
DOI: 10.3945/jn.109.108977
|View full text |Cite
|
Sign up to set email alerts
|

Isoleucine Prevents the Accumulation of Tissue Triglycerides and Upregulates the Expression of PPARα and Uncoupling Protein in Diet-Induced Obese Mice

Abstract: In this study, we investigated the effects of the branched-chain amino acid l-isoleucine (Ile) on both obesity and glucose/fat homeostasis in mice that were fed a high-fat (45% energy) diet. The mice were divided into different treatment groups and given a high-fat diet for 6 wk. During the last 4 wk, Ile was dissolved and added to the drinking water to a final concentration of 2.5%. The control mice received vehicle alone. The mice in the Ile group had an almost 6% lower body weight gain and 49% less epididym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
78
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 38 publications
11
78
0
Order By: Relevance
“…It has been shown that isoleucine supplement could prevent the tissue triglycerides accumulation (Nishimura et al 2010) and balance blood glucose (Ikehara et al 2008). For example, gavage administration of isoleucine has been shown to decrease the accumulation of tissue triglyceride via increasing expression of PPARa and UCPs (Nishimura et al 2010). Moreover, oral administration of isoleucine significantly decreased the plasma glucose concentration via stimulating glucose uptake in skeletal muscle (Doi et al 2005), in addition to decrease gluconeogenesis in liver (Doi et al 2007).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It has been shown that isoleucine supplement could prevent the tissue triglycerides accumulation (Nishimura et al 2010) and balance blood glucose (Ikehara et al 2008). For example, gavage administration of isoleucine has been shown to decrease the accumulation of tissue triglyceride via increasing expression of PPARa and UCPs (Nishimura et al 2010). Moreover, oral administration of isoleucine significantly decreased the plasma glucose concentration via stimulating glucose uptake in skeletal muscle (Doi et al 2005), in addition to decrease gluconeogenesis in liver (Doi et al 2007).…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown that isoleucine supplement could prevent the tissue triglycerides accumulation (Nishimura et al 2010) and balance blood glucose (Ikehara et al 2008). For example, gavage administration of isoleucine has been shown to decrease the accumulation of tissue triglyceride via increasing expression of PPARa and UCPs (Nishimura et al 2010).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Leucine, isoleucine, and valine are collectively referred as branched-chain amino acids (BCAAs) 4 because they share a structural feature with a branched-side chain and common initiation steps of catabolism. BCAAs have a critical function not only as common amino acid ingredients for protein synthesis but also as potent nutrient signals to regulate mammalian target of rapamycin signaling for cell growth (1), autophagy (2), glucose utilization (3), lipid metabolism (4), neurotransmitter synthesis (5), as well as skeletal muscle growth/atrophy (6), among many others.…”
mentioning
confidence: 99%
“…Feeding leucine prevented obesity in rodents 459,460 , and was associated with lower adiposity in humans 461 , while isoleucine decreased tissue TG accumulation and adiposity and increased expression of PPAR and UCPs in diet-induce obese mice 462 . Additionally, increasing BCAA levels by deletion of BCATm, the enzyme that catalyzes the first step in BCAA metabolism, completely prevents HFD-induced insulin resistance and adiposity in mice 311 .…”
Section: Discussionmentioning
confidence: 96%